THE ROLE OF THE PLEIN-AIR EXHIBITION PROJECTS IN THE DEVELOPMENT OF MODERN LANDSCAPE REALISM IN UKRAINE - Бойко , В’ячеслав (Art and Design, 2024)
Purpose of article. The purposes of the article are to study the phenomenon of modern plein-air exhibitions and analyze their impact on the formation of trends in the landscape genre in Ukrainian realistic painting. The methodology of the research involves the following methods – the historical-chronological method, classification, art analysis, and generalization. The theoretical-artistic approach has given an opportunity to analyse the materials, related to the research topic. The scientific novelty of the research is the analysis of modern Ukrainian painting in the realistic direction (namely, the landscape genre) under the influence of the national plein airs and art exhibitions of the beginning of the XXI century. Results. The article pays attention to domestic open-air exhibition projects, which have become popular among artists and fans of their works. The author highlights the following projects: the exhibition «Plenary Painting» (Lviv); the exhibition of the Youth Association of Transcarpathian Artists (Uzhhorod); All-Ukrainian art plein air «Khortytsia through the ages» (Zaporizhia); report exhibition «Mikindiv plein airs» (Uman, Cherkasy region); artistic plein air «Cultural Mosaic» (Kyiv); International art plein air «The Best Artist» (Vinnytsia); open-air exhibition «Bartka» (Kolomia, Ivano-Frankivsk region); collective exhibition of plein-air painting «The World through the Eyes of Artists» (Kyiv); Sofia Plein Air (Kyiv). Practical significance. The research allows us to state that today in Ukraine, the participation of artists in collective plein-air exhibitions and final exhibitions-presentations of plein-air works of art is one of the factors that develop the direction of realism in the fine arts. In addition, they demonstrate the spectrum of general trends in painting and graphics in Ukraine.